2017
DOI: 10.14569/ijacsa.2017.080554
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Approach towards Software Effort Estimation using Evolutionary Support Vector Machine

Abstract: Abstract-The project effort measurement is one of the most important estimates done in project management domain. This measure is done in advance using some traditional methods like Function Point analysis, Use case analysis, PERT analysis, Analogous, Poker, etc. Classical models have limitations that they are burdensome to implement, especially when there are LOC (lines of code) or objects' count required in measurement. Sometimes historical information regarding a project is also considered to estimate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…The goal of this [16] work is to give an approach for accurately estimating the time and resources required to complete a software development project using only a subset of that organization's past project data. Two techniques, the correlation matrix, and the decision tree were utilized to determine the optimal prediction parameters.…”
Section: Related Workmentioning
confidence: 99%
“…The goal of this [16] work is to give an approach for accurately estimating the time and resources required to complete a software development project using only a subset of that organization's past project data. Two techniques, the correlation matrix, and the decision tree were utilized to determine the optimal prediction parameters.…”
Section: Related Workmentioning
confidence: 99%
“…In (Mahboob et al, 2017) a solution was found to determine the effort required for a software project based on an organizations historical data for projects. The solution, based on a predictive model, is a result of research which includes two methods i.e., (a) correlation matrix and (b) decision tree.…”
Section: Related Workmentioning
confidence: 99%